Utilization of Lime Peel (Citrus aurantiifolia (Christm.) Swingle) Ethanol Extract for Mouthwash Formulation to Prevent Dental Caries - Sapitri, Alfi; Marbun, Eva Diansari; Asfianti, Vivi; Mayasari, Ulfayani (International Conference on Sciences Development and Technology, 2022)
Lime (Citrus aurantiifolia (Christm.) Swingle) is a plant that has medicinal properties. Lime peel contains alkaloids, flavonoids, tannins, steroids/triterpenoids and essential oils. These compounds are known to have antibacterial activity. This study aims to determine whether lime peel extract has antibacterial activity against Streptococcus mutans and antifungal against Candida albicans. So that an effective inhibition zone will be obtained for the manufacture of mouthwash preparations using the agar diffusion method. The research method used is the experimental method. The experiment consisted of 3 repetitions with a concentration of 96% ethanol extract of lime peel 25%, 30%, 35%, 40%, 45%. Lime peel samples were taken purposively from Pasar 1 Rel, Terjun, Kecamatan Medan Marelan, North Sumatra. The results showed that lime peel extract provided an effective inhibition zone diameter at a concentration of 40% and 45% against Streptococcus mutans with a diameter of 14.07 mm and 14.4 mm at a concentration of 40% and 45% against the fungus Candida albicans with a diameter of 14. mm and 14.2 mm in mouthwash preparations of lime peel extract at FI concentration of 40% FII concentration of 45%, giving satisfactory results of inhibition zone diameter which is greater than 14 mm against Streptococcus mutans and Candida albicans. Lime peel can be formulated in the form of mouthwash preparations.